Implementasi Model Aktivitas, Refleksi, Konseptualisasi, Dan Aplikasi (ARKA) Dalam Pembelajaran PAI - Silva Eka Diani; Asep Tutun Usman; Iman Saifullah; acep rahmat (Yayasan Al-Afif, 2025)
The learning model plays a crucial role in achieving educational goals, serving as a conceptual framework that outlines systematic procedures and acts as a guide for instructional designers. This study aims to examine the implementation of the ARKA model in Islamic Religious Education (PAI) learning at SD Garut Islamic School Prima Insani, as well as to identify the supporting and inhibiting factors in its implementation. This research is a descriptive qualitative analysis. Data were collected through observation, interviews, and documentation. Data analysis techniques included data grouping, data reduction, data presentation, and conclusion drawing. The results of this study show that: (1) The ARKA model makes PAI learning more interactive and enjoyable through games, videos, and Qur’an reading, which stimulate students’ creativity and understanding. Reflection and group discussions help students apply Islamic teachings in their daily lives. (2) PAI learning is carried out in a structured manner through planning, implementation, and evaluation using various methods, such as lectures, discussions, educational games, and projects. (3) The implementation of the ARKA model is supported by the school principal, learning resources, and regular evaluations. (4) Challenges in designing engaging activities for active students can be addressed through collaboration and the use of technology.